Corticosteroid use and the risk of glaucoma: A systematic review (Research, Society and Development, 2024)
Glaucoma is an optic neuropathy considered to be the second leading cause of vision loss in the world. Elevated intraocular pressure seems to be the main risk factor for the condition related to corticosteroids. The objective of this article was to carry out a literature review to analyze the relationship between the use of corticosteroids and the risk of glaucoma. A search was carried out in the electronic databases PubMed, SciELO, and LILACS, obtaining a total of 5090 articles. After selection based on inclusion and exclusion criteria, 15 articles were obtained as a sample. The main corticoid described was dexamethasone, in the form of an intravitreal implant. The average follow-up time was 12 months, after stopping the use of glucocorticoids, intraocular pressure returned to baseline values. It is concluded that ophthalmological follow-up of patients taking glucocorticoids is necessary to prevent persistent high levels of intraocular pressure from causing irreversible sequelae.